Effect of treadmill backward walking training on motor capacity in cerebral palsy: A randomized controlled study - Doğan, Halis; Mutluay, Fatma (Korean Academy of Rehabilitation Medicine, 2023)
Objective To evaluate treadmill backward walking training (BWT) effects on walking speed, balance, mobility, and walking endurance in children with cerebral palsy (CP). Methods The study evaluated 41 children with CP (age, 6–18; Gross Motor Function Classification System levels I and II). They were randomly allocated into control and BWT groups. BWT was applied (two sessions/week, 15 min/session for 8-week) to BWT group after the neurodevelopmental-based physiotherapy program routinely followed by all participants while the control group did not receive BWT. 10-Meter Walk Test (10MWT), Pediatric Balance Scale (PBS), Timed Up and Go Test (TUG), and Two-Minute Walk Test (2MWT) were selected as outcome measures for assessing walking speed, balance, mobility and endurance respectively. Results In BWG, 2MWT distance (3.5%), PBS (3.5%) increased significantly, and TUG decreased by 5.1% (all p<0.001) after training, 10MWT was shorter by 6.1% for BWG, corresponding to 7.4% faster walking speed (p[removed]
Keywords: Cerebral Palsy; Motor Skills; Postural Balance; Treadmill; Walking